Transport and metabolism in legume-rhizobia symbioses - Udvardi, M; Poole, P (Annual Reviews, 2013)
Symbiotic nitrogen fixation by rhizobia in legume root nodules injects about 40 million tonnes of nitrogen into agricultural systems each year. In exchange for reduced nitrogen from the bacteria, the plant reciprocates by providing rhizobia with reduced carbon and all the essential nutrients required for bacterial metabolism. Symbiotic nitrogen fixation requires exquisite integration of plant and bacterial metabolism. Central to metabolic integration are transporters of both the plant and rhizobia, which transfer elements and compounds across various plant membranes and the two bacterial membranes. Here we review current knowledge of legume and rhizobial transport and metabolism as they relate to symbiotic nitrogen fixation. Although there are common metabolic features shared by all legume-rhizobia symbioses, there are interesting differences, which show that evolution solved metabolic problems in different ways to achieve effective symbiosis in different systems. Some of these differences are described here.